Method for solidifying aeolian sand and resisting wind erosion through combination of microorganisms and sugar and calcium
The combination of microorganisms and sugar calcium in the aeolian sand solidification method addresses the inefficiencies of existing treatments by promoting uniform calcium carbonate precipitation, enhancing sand strength, and resisting erosion effectively and sustainably.
Patent Information
- Application Number
- CN202411373438.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
Existing methods for solidifying aeolian sand, such as chemical and microbial treatments, face issues with durability, environmental pollution, high costs, and instability due to environmental factors, while microbial methods have low efficiency and complexity, making them unsuitable for large-scale applications.
A method combining microorganisms with sugar calcium (MICP) to solidify aeolian sand, utilizing urease to catalyze calcium carbonate precipitation, enhancing bonding between sand particles and promoting microbial growth, with sugar calcium adjusting the reaction environment to ensure uniform precipitation.
The method achieves significant solidification and erosion resistance, is environmentally friendly, and suitable for large areas, providing stable and uniform calcium carbonate precipitation, improving the sand's strength and resistance to natural erosion.
Smart Images

Figure CN119242310A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of geotechnical engineering and geological engineering, and in particular to a method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar and calcium. Background Art
[0002] Aeolian sand is a special geological material formed under arid and semi-arid climatic conditions under the synergistic effect of wind erosion and sand source. Aeolian sand is mainly distributed in desert and semi-desert areas. The ecological environment in these areas is fragile, and wind and sand activities are frequent, which easily lead to environmental problems such as land desertification and sandstorms. The undesirable characteristics of natural aeolian sand are manifested in fine structure particles, high roundness, poor gradation, low viscosity, low bearing capacity, good water permeability and poor water retention. It is very easy to move, flow, wind erosion and liquefaction under the action of external forces. Due to the unfavorable engineering characteristics of aeolian sand, effective countermeasures should be taken to protect the current ecosystem, and solve the problem of difficulty in meeting bearing capacity and stability in engineering practice, so as to eliminate the potential safety hazards. Therefore, it is urgent to adopt targeted aeolian sand improvement methods to reinforce and improve it to meet its weather resistance and actual engineering needs. This makes it an important topic worthy of attention to strengthen the aeolian sand soil to resist the invasion of adverse conditions, thereby preventing and controlling land desertification and meeting actual engineering needs.
[0003] At present, the existing treatment methods for solidifying aeolian sand mainly include covering method, sand barrier method, chemical solidification, biological solidification, etc. For vegetation covering method and ground film covering method, the disadvantages are that they are limited by water resources, the cost of purchasing and laying covering materials and the maintenance cost are high, and the covering materials are difficult to survive or remain stable in extreme environments; for grass grid sand barrier method and stone grid sand barrier method, their own disadvantages are that they are limited by water resources, the sand barrier materials have durability problems due to wind erosion, sand burial and other reasons, and the construction is difficult; for chemical solidification method, although the solidification effect is relatively obvious, its disadvantages are that it has durability problems due to temperature changes, water evaporation and other reasons, chemical adhesives may contain harmful substances, causing pollution to the environment, and chemical adhesives are relatively expensive, and the cost is huge when used on a large scale, and the operation is difficult; the above methods have obvious disadvantages for solidifying aeolian sand, so more effective solutions should be sought for application projects.
[0004] For the microbial solidification method, microorganisms can precipitate some crystalline and non-crystalline inorganic compounds through metabolism, which play a filling and cementing role in the soil, thereby improving the soil properties. However, its solidification efficiency is relatively low, which limits its application speed and efficiency in actual engineering.
[0005] The patent application document with publication number CN 115895666A discloses a method for synergistically solidifying sand soil with MICP-modified silk fibroin, in which Bacillus pasteurianus is enriched and cultured to obtain a bacterial suspension, and part of the bacterial suspension is centrifuged to obtain a bacterial precipitate (bacterial mud); at the same time, the silk fibroin is cross-linked through a cross-linking modifier to obtain a cross-linking reaction liquid; finally, the bacterial suspension, bacterial mud, and cross-linking reaction liquid are mixed to obtain a composite suspension, and the composite suspension and the cementing liquid are cyclically perfused into the sand column sample in multiple stages, thereby improving the curing strength; however, the modified silk fibroin material used in the invention is affected by many factors in actual application, high temperature may cause silk fibroin to denature, humidity changes may affect the water absorption and degradation rate of silk fibroin, and oxygen concentration may affect the oxidative stability of silk fibroin; at the same time, the extraction and purification process of silk fibroin is relatively complicated, resulting in a high production cost; in addition, the degradation rate of silk fibroin in the natural environment is not easy to control, and may not be suitable for certain applications requiring a specific degradation rate.
[0006] Chinese invention patent application CN 116769681A discloses a method for solidifying desert aeolian sand by using a combination of bacteria and enzymes, which mainly includes the following aspects: adding two kinds of bacilli, urease, a binder and desert aeolian sand into a solidifying medium in proportion, then filling the solidifying medium into a solidifying device for solidification and air-drying, and then obtaining a solidified sand sample column for physical and chemical index analysis; however, the bacteria-enzyme combination technology involves multiple steps such as the cultivation of microorganisms, the preparation and application of enzymes, and the whole process is relatively complicated, which leads to high costs; the effect of solidifying aeolian sand by using the bacteria-enzyme combination technology is greatly affected by environmental factors, and the growth of microorganisms and the activity of enzymes are affected by multiple environmental factors such as temperature, humidity, pH value, soil type, etc. The instability of these factors may lead to a weakening of the solidification effect; the bacteria-enzyme combination technology for solidifying sand may result in a low degree of compatibility due to the selection of bacteria and urease, resulting in an unsatisfactory solidification effect. Summary of the invention
[0007] In order to overcome the defects of the above-mentioned prior art, the purpose of the present invention is to provide a method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium, and by utilizing the synergistic mechanism of MICP combined with sugar calcium, the sand body can be solidified more fully and efficiently, thereby achieving the purpose of enhancing the strength of the sand body and resisting erosion from the natural environment; in the process of solidifying the sand body with sugar calcium combined with MICP, sugar calcium can promote the growth of microorganisms and adjust the reaction environment, which is conducive to the formation of calcium carbonate precipitation, thereby playing a cementing role between sand particles, and at the same time, sugar calcium dissolves in water to release sticky substances, further making the generated calcium carbonate precipitation more uniform, and the effect of solidifying the sand body is more significant; the present invention adopts green and environmentally friendly materials, is suitable for the reinforcement of large areas of sand and soil areas, has a very significant solidification effect, has excellent characteristics of resisting erosion from the natural environment, and is widely used in the fields of sand solidification and protection.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] A method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium, specifically comprising the following steps:
[0010] Step 1: air-dry the natural aeolian sand, and then filter it through a 0.5-1 mm pore sieve to obtain a sand sample with impurities removed;
[0011] Step 2: Mix the bacterial liquid and the cementing liquid in a volume ratio of 1:1, 1:2, 2:3 or 3:2 and stir to form a solidified liquid;
[0012] Step 3: Weigh a certain mass of the sand sample prepared in step 1, add the solidifying liquid prepared in step 2, which accounts for 16% to 22% of the mass ratio of the sand sample, and mix evenly to obtain a sand material;
[0013] Step 4: Add 2% to 8% of calcium saccharide by mass to the sandy soil material obtained in step 3, and mix evenly to obtain calcium saccharide-sandy soil material;
[0014] Step 5: compact the sugar calcium-sand material obtained in step 4 in 2 to 4 layers, with each layer compacted to a height of 20 to 40 mm, perform a shaving treatment between layers, and place the material at 35 to 40° C. for curing for 5 to 7 days to obtain a cured sand body.
[0015] The method for preparing the bacterial solution in step 2 is as follows:
[0016] In a sterile environment, 0.1 g to 0.3 g of pasteurian sporosarcina is inoculated into 50 to 100 mL of liquid culture solution, and the solution is placed in a constant temperature oscillating box at 30 to 40° C. and 130 to 180 rpm for activation culture. When the liquid culture solution becomes turbid, the pasteurian sporosarcina is activated and cultured into second-generation pasteurian sporosarcina; the second-generation pasteurian sporosarcina and glycerol are uniformly mixed at a volume ratio of (5 to 7): (3 to 5), and the mixed second-generation pasteurian sporosarcina-glycerol mixed solution is placed in the liquid culture solution at a volume ratio of (1 to 2): (100 to 300) and mixed, and finally placed in a constant temperature oscillating box at 30 to 40° C. and 130 to 180 rpm for culture to obtain a bacterial solution;
[0017] The preparation method of the liquid culture solution is:
[0018] Manganese sulfate, nickel chloride, ammonium chloride, yeast extract and deionized water are uniformly mixed in a mass ratio of (1-2):(1-2):(1000-2000):(2000-4000):(100000-200000), adjusted to pH=8.0-9.0 with NaOH solution, placed in steam for heating and sterilization for 30-45 minutes, and then placed at room temperature for cooling for later use.
[0019] The preparation method of the cementing liquid in step 2 is:
[0020] The urea solution of equal concentration and volume and the anhydrous calcium chloride solution are uniformly mixed to obtain a cementing solution with a concentration of 1 to 2.5 mol / L.
[0021] The beneficial effects of the present invention are:
[0022] (1) The present invention improves and solidifies aeolian sand by combining MICP with calcium saccharide. The urease secreted by Sporosarcina pasteurii under suitable environmental conditions is used. The urease catalyzes the hydrolysis of urea to produce carbonate ions and ammonium ions. The carbonate ions produced by the hydrolysis combine with the calcium ions produced by the hydrolysis of calcium chloride to form calcium carbonate precipitates. The calcium carbonate precipitates play a cementing role between sand particles. The dissolution of calcium saccharide in water releases sticky substances, which can help the adhesion between particles. At the same time, calcium saccharide can promote the growth of microorganisms and adjust the reaction environment. Through physical bonding, water property adjustment and mechanical property enhancement, the land desertification can be prevented and controlled and the actual engineering needs can be met. The invention has the advantages of enhancing the solidification strength of aeolian sand and resisting the erosion of the natural environment.
[0023] (2) Compared with traditional reinforcement methods, the consolidation of aeolian sandy soil by MICP combined with sugar calcium can not only significantly improve the consolidation effect and improve the erosion capacity of the natural environment to prevent and control land desertification, but also achieve green, environmentally friendly, pollution-free and sustainable resource utilization, especially when reinforcing large areas.
[0024] (3) Compared with the MICP combined with modified protein solidification method, the addition of sugar calcium in the present invention ensures that the MICP reaction is more fully carried out in the sand body, and the reaction rate is easier to control, avoiding the occurrence of local uneven solidification. The solidified sand structure is more stable and has higher strength. In practical applications, due to the good stability of sugar calcium itself, it is less affected by temperature, humidity and oxygen concentration and has stronger adaptability.
[0025] (4) Compared with the method of solidifying desert aeolian sand by combining bacteria and enzymes, the present invention uses the synergistic effect of sugar calcium and MICP to cement the sand and soil, thereby controlling the metabolic activities and self-regulation mechanisms of microorganisms, thereby better responding to environmental changes; at the same time, the reaction rate of sugar calcium combined with MICP to generate calcium carbonate precipitation is easier to control, and the generated calcium carbonate precipitate is more uniform.
[0026] In summary, in the process of curing the sand body by combining sugar calcium with MICP of the present invention, sugar calcium can promote the growth of microorganisms and adjust the reaction environment, which is conducive to the formation of calcium carbonate precipitation, thereby playing a cementing role between sand particles. At the same time, sugar calcium dissolves in water to release sticky substances, further making the generated calcium carbonate precipitation more uniform, and the effect of curing the sand body is more significant; the present invention adopts green and environmentally friendly materials, is suitable for the reinforcement of large-area sand areas, has a very significant curing effect, has excellent characteristics of resisting natural environmental erosion, and is widely used in the fields of sand curing and protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a flow chart for preparing a solidified sand body;
[0028] Figure 2 This is a particle size distribution diagram of the sand sample after weathering and removal of impurities in the present invention;
[0029] Figure 3 It is a comparison chart of calcium carbonate production and unconfined compressive strength of the MICP combined with sugar calcium orthogonal test of the present invention; wherein, Figure 3 (a) is a comparison chart of calcium carbonate production and unconfined compressive strength when the volume ratio of bacterial liquid to cementing liquid is 1:1; Figure 3 (b) is a comparison chart of calcium carbonate production and unconfined compressive strength when the volume ratio of bacterial liquid to cementing liquid is 1:2; Figure 3 (c) is a comparison chart of calcium carbonate production and unconfined compressive strength when the volume ratio of bacterial liquid to cementing liquid is 2:3; Figure 3 (d) is a comparison chart of calcium carbonate production and unconfined compressive strength when the volume ratio of bacterial liquid to cementing liquid is 3:2;
[0030] Figure 4 It is the peak value and stress-strain curve of the MICP combined with sugar calcium reinforcement sample of the present invention; wherein, Figure 4 (a) shows the peak value and stress-strain curve when the volume ratio of bacterial liquid to cementing liquid is 1:1; Figure 4 (b) is the peak value and stress-strain curve when the volume ratio of bacterial liquid to cementing liquid is 1:2; Figure 4 (c) shows the peak value and stress-strain curve when the volume ratio of bacterial liquid to cementing liquid is 2:3; Figure 4 (d) is the peak value and stress-strain curve when the volume ratio of bacterial liquid to cementing liquid is 3:2;
[0031] Figure 5 This is a physical picture of the wind tunnel test machine of the present invention;
[0032] Figure 6 The sand-filled tray placed in the wind tunnel model test of the present invention;
[0033] Figure 7 It is a schematic diagram of the original aeolian sand tray of the present invention;
[0034] Figure 8 This is a test diagram of the wind erosion resistance of the original wind-blown sand tray of the present invention under different wind speeds and different blowing times; wherein, Figure 8 (a) is the wind erosion resistance test diagram under wind speed of 6m / s and erosion for 5min; Figure 8 (b) is the wind erosion resistance test diagram under the conditions of wind speed of 6m / s and erosion for 10min;
[0035] Figure 8 (c) is the wind erosion resistance test diagram under the conditions of wind speed of 6m / s and erosion for 15min; Figure 8 (d) is the wind erosion resistance test diagram under wind speed of 9m / s and erosion for 5min; Figure 8 (e) is the wind erosion resistance test diagram under wind speed of 9m / s and erosion for 10min; Figure 8 (f) is the wind erosion resistance test diagram under wind speed of 9m / s and erosion for 15min; Figure 8 (g) is the wind erosion resistance test diagram under wind speed of 12m / s and erosion for 5min; Figure 8 (h) is the wind erosion resistance test diagram under wind speed of 12m / s and erosion for 10min; Figure 8 (i) is the wind erosion resistance test diagram under wind speed of 12m / s and erosion for 15min;
[0036] Fig. 9 It is a bar graph of the mass loss amount and mass loss rate of the original aeolian sand tray after wind erosion of the present invention;
[0037] Fig.10 It is a schematic diagram of the aeolian sand tray after solidification of the present invention;
[0038] Fig.11 This is a test diagram of the wind erosion resistance of the aeolian sand tray after solidification of the present invention under different wind speeds and different blowing times; wherein, Fig.11 (a) is the wind erosion resistance test diagram under wind speed of 6m / s and erosion for 5min; Fig.11 (b) is the wind erosion resistance test diagram under the conditions of wind speed of 6m / s and erosion for 10min; Fig.11 (c) is the wind erosion resistance test diagram under the conditions of wind speed of 6m / s and erosion for 15min; Fig.11 (d) is the wind erosion resistance test diagram under wind speed of 9m / s and erosion for 5min; Fig.11 (e) is the wind erosion resistance test diagram under wind speed of 9m / s and erosion for 10min; Fig.11 (f) is the wind erosion resistance test diagram under wind speed of 9m / s and erosion for 15min; Fig.11(g) is the wind erosion resistance test diagram under wind speed of 12m / s and erosion for 5min; Fig.11 (h) is the wind erosion resistance test diagram under wind speed of 12m / s and erosion for 10min; Fig.11 (i) is the wind erosion resistance test diagram under wind speed of 12m / s and erosion for 15min;
[0039] Fig.12 A bar graph showing the mass loss amount and mass loss rate of the aeolian sand disk after wind erosion after solidification of the present invention;
[0040] Fig.13 The figure is a comparative bar graph of the surface strength of the aeolian sand tray after solidification before and after wind erosion. DETAILED DESCRIPTION
[0041] The following will be combined with the accompanying drawings in the present invention and accompanied by text descriptions to clearly and completely explain the methods, processes and effects in the embodiments of the present invention.
[0042] Example 1
[0043] See also Figure 1 , a method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium, specifically comprising the following steps:
[0044] Step 1: air-dry the natural aeolian sand, and then filter it through a 0.5 mm mesh sieve to obtain a sand sample with impurities removed;
[0045] According to the Civil Engineering Test Procedure, the mechanical properties of the sand sample were measured. After the natural aeolian sand was air-dried, the particles larger than 1 mm and their impurities were removed. The content of particles with a diameter of 0.05 mm to 0.5 mm was 96%, the dry density was 1.52 g / cm3, Cu = 2.25, Cc = 0.73, and the particle size distribution of the sand sample was as follows: Figure 2 As shown;
[0046] Step 2: Mix the bacterial liquid and the cementing liquid in a volume ratio of 1:1 and stir to form a solidifying liquid;
[0047] The bacterial liquid preparation method is as follows:
[0048] In a sterile environment, 0.1 g of pasteurian sporosarcina is inoculated into 50 mL of liquid culture solution, and the solution is placed in a constant temperature oscillating box at 30°C and 180 rpm for activation culture. When the liquid culture solution becomes turbid, the pasteurian sporosarcina is activated and cultured into the second-generation pasteurian sporosarcina; the second-generation pasteurian sporosarcina and glycerol are uniformly mixed at a volume ratio of 7:3, and then the mixed second-generation pasteurian sporosarcina-glycerol mixed solution is placed in the liquid culture solution at a volume ratio of 1:100, and finally placed in a constant temperature oscillating box at 30°C and 180 rpm for culture to obtain a bacterial solution;
[0049] The preparation method of the liquid culture solution is:
[0050] Manganese sulfate, nickel chloride, ammonium chloride, yeast extract and deionized water were uniformly mixed in a mass ratio of 1:1:1000:2000:100000, adjusted to pH = 9.0 with 1 mol / L NaOH solution, heated and sterilized in steam for 35 minutes, and then cooled at room temperature for later use;
[0051] The preparation method of the cementing liquid is:
[0052] The urea solution of equal concentration and volume was uniformly mixed with the anhydrous calcium chloride solution to obtain a cementing solution with a concentration of 1 mol / L;
[0053] Step 3: Weigh a certain mass of the sand sample prepared in step 1, add the solidifying liquid prepared in step 2, which accounts for 16% of the mass ratio of the sand sample, and mix evenly to obtain a sand material;
[0054] Step 4: Add 2% of calcium saccharide by mass to the sandy soil material obtained in step 3, and mix evenly to obtain calcium saccharide-sandy soil material;
[0055] The sugar calcium is obtained through commercial channels (brand: Qingjun, model: slow setting and water reduction), and is a brown-yellow powder solid made from sugar factory waste (waste molasses, lees) and other raw materials. It is a polymer electrolyte with a molecular weight of 1000-100000, among which the dispersibility of 10000-40000 is particularly effective. The sugar calcium has strong decomposition, adhesion and assimilation properties;
[0056] Sugar calcium is mainly divided into sucrose calcium complex and monosaccharide calcium complex. When dissolved in water, it releases viscous substances (monosaccharides and sucrose) and Ca 2+ , which helps to bond sand particles together, while sugar calcium can promote microbial growth and adjust the reaction environment;
[0057] Step 5: compact the sugar calcium-sand material obtained in step 4 in 3 layers, with each layer compacted to a height of 27 mm. Scrape the layers apart, and place at 35° C. for 7 days to solidify and cure to obtain a solidified sand body.
[0058] Example 2
[0059] A method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium, specifically comprising the following steps:
[0060] Step 1: air-dry the natural aeolian sand, and then filter it through a 0.6 mm mesh sieve to obtain a sand sample with impurities removed;
[0061] Step 2: Mix the bacterial liquid and the cementing liquid in a volume ratio of 1:2 and stir to form a solidifying liquid;
[0062] The bacterial liquid preparation method is as follows:
[0063] In a sterile environment, 0.2 g of pasteurian sporosarcina is inoculated into 50 mL of liquid culture solution, and the solution is placed in a constant temperature shaking box at 35°C and 170 rpm for activation culture. When the liquid culture solution becomes turbid, the pasteurian sporosarcina is activated and cultured into the second-generation pasteurian sporosarcina; the second-generation pasteurian sporosarcina and glycerol are uniformly mixed at a volume ratio of 6:4, and then the mixed second-generation pasteurian sporosarcina-glycerol mixed solution is placed in the liquid culture solution at a volume ratio of 1.5:200, and finally placed in a constant temperature shaking box at 35°C and 170 rpm for culture to obtain a bacterial solution;
[0064] The preparation method of the liquid culture solution is:
[0065] Manganese sulfate, nickel chloride, ammonium chloride, yeast extract and deionized water were uniformly mixed in a mass ratio of 1:1.5:2000:3000:150000, adjusted to pH=8.5 with 1 mol / L NaOH solution, heated and sterilized in steam for 30 min, and then cooled at room temperature for later use;
[0066] The preparation method of the cementing liquid is:
[0067] The urea solution of equal concentration and volume was uniformly mixed with the anhydrous calcium chloride solution to obtain a cementing solution with a concentration of 1.5 mol / L;
[0068] Step 3: Weigh a certain mass of the sand sample prepared in step 1, add the solidifying liquid prepared in step 2, which accounts for 18% of the mass ratio of the sand sample, and mix evenly to obtain a sand material;
[0069] Step 4: Add 4% of sugar calcium to the sandy soil material obtained in step 3, and mix evenly to obtain sugar calcium-sandy soil material;
[0070] Step 5: compact the sugar calcium-sand material obtained in step 4 in 4 layers, with each layer compacted to a height of 20 mm. Scrape the layers apart, and place at 37° C. for 6 days to solidify and cure, to obtain a solidified sand body.
[0071] Example 3
[0072] A method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium, specifically comprising the following steps:
[0073] Step 1: air-dry the natural aeolian sand, and then filter it through a 0.7 mm mesh sieve to obtain a sand sample with impurities removed;
[0074] Step 2: Mix the bacterial liquid and the cementing liquid in a volume ratio of 2:3 and stir to form a solidifying liquid;
[0075] The bacterial liquid preparation method is as follows:
[0076] In a sterile environment, 0.2 g of pasteurian sporosarcina is inoculated into 100 mL of liquid culture solution, and the solution is placed in a constant temperature shaking box at 40°C and 160 rpm for activation culture. When the liquid culture solution becomes turbid, the pasteurian sporosarcina is activated and cultured into the second-generation pasteurian sporosarcina; the second-generation pasteurian sporosarcina and glycerol are uniformly mixed at a volume ratio of 5:4, and then the mixed second-generation pasteurian sporosarcina-glycerol mixed solution is placed in the liquid culture solution at a volume ratio of 2:300, and finally placed in a constant temperature shaking box at 40°C and 160 rpm for culture to obtain a bacterial solution;
[0077] The preparation method of the liquid culture solution is:
[0078] Manganese sulfate, nickel chloride, ammonium chloride, yeast extract and deionized water were uniformly mixed in a mass ratio of 2:2:1500:3000:200000, adjusted to pH=8.0 with 1 mol / L NaOH solution, heated and sterilized in steam for 40 min, and then cooled at room temperature for later use;
[0079] The preparation method of the cementing liquid is:
[0080] The urea solution of equal concentration and volume and the anhydrous calcium chloride solution are uniformly mixed to obtain a cementing solution with a concentration of 2 mol / L;
[0081] Step 3: Weigh a certain mass of the sand sample prepared in step 1, add the solidifying liquid prepared in step 2, which accounts for 18% of the mass ratio of the sand sample, and mix evenly to obtain a sand material;
[0082] Step 4: Add 6% of calcium saccharide by mass to the sandy soil material obtained in step 3, and mix evenly to obtain calcium saccharide-sandy soil material;
[0083] Step 5: compact the sugar calcium-sand material obtained in step 4 in 2 layers, with each layer compacted to a height of 40 mm. Scrape the layers apart, and place at 39° C. for curing for 5 days to obtain a cured sand body.
[0084] Example 4
[0085] A method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium, specifically comprising the following steps:
[0086] Step 1: air-dry the natural aeolian sand, and then filter it through a 0.8 mm mesh sieve to obtain a sand sample with impurities removed;
[0087] Step 2: Mix the bacterial liquid and the cementing liquid in a volume ratio of 2:3 and stir to form a solidifying liquid;
[0088] The bacterial liquid preparation method is as follows:
[0089] In a sterile environment, 0.2 g of pasteurian sporosarcina is inoculated into 50 mL of liquid culture solution, and the solution is placed in a constant temperature shaking box at 35°C and 150 rpm for activation culture. When the liquid culture solution becomes turbid, the pasteurian sporosarcina is activated and cultured into the second-generation pasteurian sporosarcina; the second-generation pasteurian sporosarcina and glycerol are uniformly mixed at a volume ratio of 5:3, and then the mixed second-generation pasteurian sporosarcina-glycerol mixed solution is placed in the liquid culture solution at a volume ratio of 2:100, and finally placed in a constant temperature shaking box at 35°C and 150 rpm for culture to obtain a bacterial solution;
[0090] The preparation method of the liquid culture solution is:
[0091] Manganese sulfate, nickel chloride, ammonium chloride, yeast extract and deionized water were uniformly mixed in a mass ratio of 2:1:1000:4000:150000, adjusted to pH = 9.0 with 1 mol / L NaOH solution, heated and sterilized in steam for 45 minutes, and then cooled at room temperature for later use;
[0092] The preparation method of the cementing liquid is:
[0093] The urea solution of equal concentration and volume and the anhydrous calcium chloride solution are uniformly mixed to obtain a cementing solution with a concentration of 2 mol / L;
[0094] Step 3: Weigh a certain mass of the sand sample prepared in step 1, add the solidifying liquid prepared in step 2, which accounts for 20% of the mass ratio of the sand sample, and mix evenly to obtain a sand material;
[0095] Step 4: Add 6% of calcium saccharide by mass to the sandy soil material obtained in step 3, and mix evenly to obtain calcium saccharide-sandy soil material;
[0096] Step 5: compact the sugar calcium-sand material obtained in step 4 in 3 layers, with each layer compacted to a height of 27 mm. Scrape the layers apart, and place at 40° C. for 7 days to solidify and cure to obtain a solidified sand body.
[0097] Example 5
[0098] A method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium, specifically comprising the following steps:
[0099] Step 1: air-dry the natural aeolian sand, and then filter it through a 1.0 mm mesh sieve to obtain a sand sample with impurities removed;
[0100] Step 2: Mix the bacterial liquid and the cementing liquid in a volume ratio of 3:2 and stir to form a solidifying liquid;
[0101] The bacterial liquid preparation method is as follows:
[0102] In a sterile environment, 0.1 g of pasteurian sporosarcina is inoculated into 100 mL of liquid culture solution, and the solution is placed in a constant temperature shaking box at 30°C and 130 rpm for activation culture. When the liquid culture solution becomes turbid, the pasteurian sporosarcina is activated and cultured into the second-generation pasteurian sporosarcina; the second-generation pasteurian sporosarcina and glycerol are uniformly mixed at a volume ratio of 5:5, and then the mixed second-generation pasteurian sporosarcina-glycerol mixed solution is placed in the liquid culture solution at a volume ratio of 1:300, and finally placed in a constant temperature shaking box at 30°C and 130 rpm for culture to obtain a bacterial solution;
[0103] The preparation method of the liquid culture solution is:
[0104] Manganese sulfate, nickel chloride, ammonium chloride, yeast extract and deionized water were uniformly mixed in a mass ratio of 2:2:2000:3000:200000, adjusted to pH=8.5 with 1 mol / L NaOH solution, heated and sterilized in steam for 35 minutes, and then cooled at room temperature for later use;
[0105] The preparation method of the cementing liquid is:
[0106] The urea solution of equal concentration and volume was uniformly mixed with the anhydrous calcium chloride solution to obtain a cementing solution with a concentration of 2.5 mol / L;
[0107] Step 3: Weigh a certain mass of the sand sample prepared in step 1, add the solidifying liquid prepared in step 2, which accounts for 22% of the mass ratio of the sand sample, and mix evenly to obtain a sand material;
[0108] Step 4: Add 8% of sugar calcium to the sandy soil material obtained in step 3, and mix evenly to obtain sugar calcium-sandy soil material;
[0109] Step 5: compact the sugar calcium-sand material obtained in step 4 in 4 layers, with each layer compacted to a height of 20 mm. Scrape the layers apart, and place at 35° C. for curing for 5 days to obtain a cured sand body.
[0110] Test verification
[0111] In order to explore the key influencing factors and effects of the microorganism combined with sugar calcium in the present invention for solidifying aeolian sand and resisting wind erosion: by considering the volume ratio of the mixed solution of bacterial liquid and cementing liquid (1:1, 1:2, 2:3, 3:2), the concentration of cementing liquid (1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L), the mass ratio of the solidifying liquid added to the sand (16%, 18%, 20%, 22%), and the amount of sugar calcium added (2%, 4%, 6%, 8%), the following experiment was designed:
[0112] The test plan is shown in Table 1 below:
[0113] Table 1 Orthogonal test scheme for key influencing factors of MICP combined with sugar-calcium solidification of sand
[0114]
[0115]
[0116] According to the requirements of the test scheme in Table 1, the mixture of the bacterial liquid and the binder liquid was mixed and stirred in a volume ratio of 1:1, 1:2, 2:1, and 2:3 to prepare a solidifying liquid, a certain mass of sandy soil sample was weighed, and 16% to 22% of the solidifying liquid and 2% to 8% of the sugar calcium were added to the sandy soil sample and mixed evenly to obtain a sugar calcium-sandy soil material; the sugar calcium-sandy soil material was compacted in layers, the layers were scraped and cured, and the layers were left to solidify and cure to obtain a solidified sandy soil body.
[0117] Take the solidified sandy soil obtained by the above test scheme, and use 1mol / L hydrochloric acid to fully pickle it to measure the content of calcium carbonate. The specific operation is: accurately weigh a certain amount of solidified and cured sugar calcium-sandy soil material and put it into a conical flask, add a sufficient amount of dilute hydrochloric acid to the conical flask, so that the calcium carbonate in the sample reacts with the hydrochloric acid to generate carbon dioxide gas, and observe the reaction of the sample with the acid. The carbon dioxide gas generated by the reaction will form bubbles. After observing that no bubbles are generated, wash the filter residue with a small amount of distilled water to ensure that all soluble substances enter the filtrate, and then put the filter residue into a dryer to dry and weigh it. The original sample mass minus the mass of the filter residue after drying is the amount of calcium carbonate generated by the reaction.
[0118] Referring to GB / T50123-2019 "Standard for Geotechnical Test Methods", an unconfined compressive strength test was carried out on the solidified sandy soil obtained by the above test scheme using a strain-controlled unconfined compression testing machine at a loading rate set to 1 mm / min to obtain the compressive strength of the solidified sandy soil.
[0119] Table 2 Calcium carbonate production and compressive strength of MICP combined with sugar calcium orthogonal test
[0120]
[0121] According to the data analysis of Table 2 above, it can be concluded that the amount of sugar calcium added to sand and the mass ratio of the solidifying liquid added to the sand play a major role in affecting the strength of the sand and the amount of calcium carbonate generated. The concentration of the cementing liquid and the volume ratio of the mixed liquid of the bacterial liquid and the cementing liquid have little effect on the strength of the sand and the amount of calcium carbonate generated. Therefore, the order of influence of the above three factors on the strength of the sand and the amount of calcium carbonate generated is: the amount of sugar calcium added to the sand> the mass ratio of the solidifying liquid added to the sand> the concentration of the cementing liquid> the volume ratio of the bacterial liquid and the cementing liquid.
[0122] With the increase of sugar calcium addition, the strength and calcium carbonate content of the sample increased significantly, and the strength and calcium carbonate content of the sample generally showed a positive correlation. Figure 3 From the analysis of (a)-(d) in Figure 1, it can be seen that when the amount of sugar calcium added is 6%, it exceeds 3000kPa, and when the amount is 8%, the strength is close to that when the amount is 6%. Compared with the compressive strength of the sand sample without the addition of solidifying materials, it increases by about 1400%. With the increase of the amount of sugar calcium added, when the amount reaches 6%, the calcium carbonate content can reach 17.1%. This is because the sugar calcium will dissolve in the liquid during the reinforcement process and decompose the free Ca 2 + , providing a more adequate source of calcium for the microbial process to react with.
[0123] according to Figure 4 From the analysis of (a)-(d) in the figure, it can be seen that no matter what the dosage is, the stress-strain curve of sugar calcium-sand material also has obvious values, which is a strain softening type, and there are mainly three stages: stress rise, stress drop and residual stress. When the dosage of sugar calcium is 2%, the effect on the curing effect is small, and the residual strength is about 280kPa. As the dosage of sugar calcium gradually increases, the curve gradually moves up. When the dosage reaches 6%, the strain corresponding to the peak stress of the sample is 0.025%, and the slope of the curve of the sample in the stress rise section increases significantly. In the stress section, it shows a higher residual strength of about 550kPa, indicating that the addition of sugar calcium has improved the ability to resist deformation to a certain extent, and its contribution to the peak strength is the most obvious.
[0124] Preferably, the combination of MICP combined with sugar-calcium solidification to obtain the strength, cementing content and component yield per unit volume of sand is selected as follows: the volume ratio of the mixture of bacterial liquid and cementing liquid is 1:1, the concentration of the cementing liquid is 2 mol / L, the mass ratio of the solidifying liquid added to the sand is 20%, and the sugar-calcium dosage in the sand can be 6%.
[0125] like Figure 5 , Figure 6 As shown in the figure, in order to explore the effect of MICP combined with sugar calcium to solidify aeolian sand against wind erosion, the present invention made a sand-filled tray with a length, width and height of 28 cm, 20 cm and 2 cm, respectively, and a surface area of 560 cm 2 , the volume of the sandbox is 1120cm 3 . According to the dry density of 1.48g / cm 3 The sand tray was prepared under the conditions of , and the total weight of the sand tray was 1657g.
[0126] like Figure 7 and Figure 8As shown in (a)-(i) in the figure, in order to better observe the anti-wind erosion characteristics of aeolian sand under extreme conditions, the test of the present invention adopts three wind erosion cycles of 1, 2, and 3 times, and stipulates that the anti-wind erosion characteristics at three different speeds of 6m / s, 9m / s, and 12m / s are processed at a frequency of 5min / time.
[0127] Take natural aeolian sand, dry it, and filter it with a 0.5 mm mesh sieve to obtain a sand sample with impurities removed (i.e., original aeolian sand). Fill the sand sample (1530 g in total) into the above-mentioned sand-filling tray and place it in a wind tunnel tester for a wind tunnel model test. The test results are as follows:
[0128] Table 3 Wind erosion resistance test characteristics of original wind-blown sand tray
[0129]
[0130]
[0131] like Fig.10 and Fig.11 As shown in (a)-(i) in the figure, the sand sample (a total of 1530g) in the sand tray was subjected to MICP combined with calcium sugar spray reinforcement treatment, and the volume ratio of bacterial liquid to cementing liquid was selected to be 1:1, the concentration of cementing liquid was 2mol / L, the solidifying liquid accounted for 20% of the mass ratio of the sand sample, and the calcium sugar accounted for 6% of the mass ratio of the sand sample. They were sprayed on the aeolian sand tray in sequence according to the above proportions, and left to stand for curing at 35°C for 7 days to obtain the cured aeolian sand. Referring to the standard ASTM G113, the aeolian sand tray cured by MICP combined with calcium sugar spray was treated with wind tunnel model test for wind erosion resistance, and the experimental results are as follows:
[0132] Table 4 Anti-wind erosion properties of aeolian sand tray after curing
[0133]
[0134]
[0135] According to Tables 3 and 4 above, it can be seen that through the wind erosion resistance test of the original aeolian sand disk and the solidified aeolian sand disk under the same conditions, it is concluded that the mass loss of the aeolian sand sample gradually increases with the increase of the number of wind erosion cycles, and the mass loss of the aeolian sand sample also increases with the continuous increase of wind speed. The increase of the number of wind erosion cycles and the increase of wind speed have little effect on the surface hardness of the solidified aeolian sand disk.
[0136] According to the above Table 3 and Figure 8From (a)-(i) in the figure, we can see that for the original aeolian sand disk, when the wind speed is 9m / s and the erosion time is 10min, the aeolian sand disk has been completely eroded. The reason for the above is that the particle size of aeolian sand is small and it is easy to be blown up by the wind. Especially when the sand is dry, the bonding force between the sand particles is reduced. When the wind speed reaches a level sufficient to transport the sand, the sand will be blown up from the sand dunes or the ground, which is very easy to form wind erosion, thus affecting the landform and causing a series of environmental problems such as land degradation and frequent sandstorms.
[0137] according to Fig. 9 It can be seen that for the original aeolian sand disk, when the wind speed is 6m / s and the erosion time is 15min, the mass loss of the original aeolian sand disk reaches 1320g, and the mass loss rate reaches 86%. When the wind speed is 9m / s and 12m / s and the erosion time is 5min, the mass loss of the original aeolian sand disk is almost complete, and the mass loss rate is about 100%. The surface hardness of the original aeolian sand disk can be regarded as 0 before and after erosion.
[0138] According to the above Table 4 and Fig.11 (a)-(i) in it: For the solidified aeolian sand tray, it exhibits excellent wind erosion resistance compared to the original aeolian sand model. Under extreme conditions of wind speed of 12m / s and erosion time of 15min, the mass loss and the reduction in surface strength of the aeolian sand tray after wind erosion are negligible. The reason for the above is that the aeolian sand after the treatment of sugar calcium and MICP reinforcement is to cement the sand particles together to form a dense protective layer. Under their joint action, it can effectively prevent and control environmental problems such as land desertification and sandstorms caused by wind erosion of aeolian sand. Therefore, the solidified aeolian sand tray exhibits excellent wind erosion resistance and can fully meet the purpose of wind erosion resistance.
[0139] according to Fig.12 and Fig.13 It can be seen that the solidified aeolian sand disc exhibits excellent anti-wind erosion properties. When the wind speed is 6m / s and the erosion time is 15min, the mass loss of the solidified aeolian sand disc is only 3.52g, and the mass loss rate is 0.23%. When the wind speed is 12m / s and the erosion time is 15min, the mass loss of the solidified aeolian sand disc is only 4.58g, and the mass loss rate is 0.30%. The hardness of the solidified aeolian sand disc is reduced from 343kPa to 337kPa under the conditions of wind speed of 12m / s and erosion time of 15min, and the hardness loss rate is only 1.7%.
[0140] Compared with the mass loss rate of the original aeolian sand disk in the wind erosion test, the cumulative mass loss rate of the solidified aeolian sand disk was reduced by 333 times.
[0141] In summary, the use of 6% sugar-calcium combined with MICP technology (the volume ratio of the mixture of bacterial liquid and binder is 1:1, the concentration of binder is 2 mol / L, and the mass ratio of the solidifying liquid added to the sand is 20%) to solidify sand can effectively prevent the wind erosion of aeolian sand, thereby effectively preventing environmental problems such as land desertification and sandstorms caused by wind erosion of aeolian sand.
[0142] It can be seen from the above embodiments that compared with the prior art:
[0143] The invention improves and solidifies aeolian sand by combining MICP with sugar calcium. Sporosarcina pasteurii secretes urease under suitable environmental conditions. Urease catalyzes the hydrolysis of urea to produce carbonate ions and ammonium ions. The carbonate ions produced by the hydrolysis combine with the calcium ions produced by the hydrolysis of calcium chloride to form calcium carbonate precipitation. The calcium carbonate precipitation plays a cementing role between sand particles. The dissolution of sugar calcium in water releases sticky substances, which can help the adhesion between particles. At the same time, the sugar calcium can promote the growth of microorganisms and adjust the reaction environment. Through physical bonding, water property adjustment and mechanical property enhancement, the land desertification can be prevented and controlled and the actual engineering needs can be met. The invention has the advantages of enhancing the solidification strength of aeolian sand body and resisting the erosion of the natural environment.
[0144] Compared with traditional reinforcement methods, the consolidation of aeolian sandy soil through MICP combined with sugar calcium can not only significantly improve the solidification effect and improve the erosion capacity of the natural environment to prevent and control land desertification, but also achieve green, environmentally friendly, pollution-free and sustainable use of resources, especially when reinforcing large areas.
[0145] Compared with the MICP combined with modified protein solidification method, the addition of sugar calcium in the present invention ensures that the MICP reaction is more fully carried out in the sand body, and the reaction rate is easier to control, avoiding the occurrence of local uneven solidification, and the solidified sand structure is more stable and has higher strength; in practical applications, due to the good stability of sugar calcium itself, it is less affected by temperature, humidity and oxygen concentration, and has stronger adaptability.
[0146] Compared with the method of solidifying desert aeolian sand by combining bacteria and enzymes, the present invention uses the synergistic effect of sugar calcium and MICP to cement the sandy soil, thereby controlling the metabolic activities and self-regulatory mechanisms of microorganisms, thereby better coping with environmental changes; at the same time, the reaction rate of sugar calcium combined with MICP to generate calcium carbonate precipitation is easier to control, and the generated calcium carbonate precipitation is more uniform.
[0147] In summary, in the process of curing the sand body by combining sugar calcium with MICP of the present invention, sugar calcium can promote the growth of microorganisms and adjust the reaction environment, which is conducive to the formation of calcium carbonate precipitation, thereby playing a cementing role between sand particles. At the same time, sugar calcium dissolves in water to release sticky substances, further making the generated calcium carbonate precipitation more uniform, and the effect of curing the sand body is more significant; the present invention adopts green and environmentally friendly materials, is suitable for the reinforcement of large-area sand areas, has a very significant curing effect, has excellent characteristics of resisting natural environmental erosion, and is widely used in the fields of sand curing and protection.
[0148] The present invention and its embodiments are described above, which is not restrictive. The drawings are only one of the embodiments of the present invention. In short, if ordinary technicians in the field are inspired by it and design structural methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium, characterized in that: The specific steps include: Step 1: air-dry the natural aeolian sand, and then filter it through a 0.5-1 mm mesh sieve to obtain a sand sample with impurities removed; Step 2: Mix the bacterial liquid and the cementing liquid in a volume ratio of 1:1, 1:2, 2:3 or 3:2 and stir to form a solidified liquid; Step 3: Weigh a certain mass of the sand sample prepared in step 1, add the solidifying liquid prepared in step 2, which accounts for 16% to 22% of the mass ratio of the sand sample, and mix evenly to obtain a sand material; Step 4: Add 2% to 8% of calcium saccharide by mass to the sandy soil material obtained in step 3, and mix evenly to obtain calcium saccharide-sandy soil material; Step 5: compact the sugar calcium-sand material obtained in step 4 in 2 to 4 layers, with each layer compacted to a height of 20 to 40 mm, perform a shaving treatment between layers, and place the material at 35 to 40° C. for curing for 5 to 7 days to obtain a cured sand body.
2. The method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium according to claim 1, characterized in that: The method for preparing the bacterial solution in step 2 is: In a sterile environment, 0.1 g to 0.3 g of pasteurian sporosarcina is inoculated into 50 to 100 mL of liquid culture solution, and the solution is placed in a constant temperature oscillating box at 30 to 40° C. and 130 to 180 rpm for activation culture. When the liquid culture solution becomes turbid, the pasteurian sporosarcina is activated and cultured into second-generation pasteurian sporosarcina; the second-generation pasteurian sporosarcina and glycerol are uniformly mixed at a volume ratio of (5 to 7): (3 to 5), and the mixed second-generation pasteurian sporosarcina-glycerol mixed solution is placed in the liquid culture solution at a volume ratio of (1 to 2): (100 to 300) and mixed, and finally placed in a constant temperature oscillating box at 30 to 40° C. and 130 to 180 rpm for culture to obtain a bacterial solution; The preparation method of the liquid culture solution is: Manganese sulfate, nickel chloride, ammonium chloride, yeast extract and deionized water are uniformly mixed in a mass ratio of (1-2):(1-2):(1000-2000):(2000-4000):(100000-200000), adjusted to pH=8.0-9.0 with NaOH solution, placed in steam for heating and sterilization for 30-45 minutes, and then placed at room temperature for cooling for later use.
3. The method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium according to claim 1, characterized in that: The preparation method of the cementing liquid in step 2 is: The urea solution of equal concentration and volume is uniformly mixed with the anhydrous calcium chloride solution to obtain a cementing solution with a concentration of 1 to 2.5 mol / L.
4. A method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium, characterized in that: The specific steps include: Step 1: air-dry the natural aeolian sand, and then filter it through a 0.5 mm mesh sieve to obtain a sand sample with impurities removed; Step 2: Mix the bacterial liquid and the cementing liquid in a volume ratio of 1:1 and stir to form a solidifying liquid; The bacterial liquid preparation method is as follows: In a sterile environment, 0.1 g of pasteurian sporosarcina is inoculated into 50 mL of liquid culture solution, and the solution is placed in a constant temperature oscillating box at 30°C and 180 rpm for activation culture. When the liquid culture solution becomes turbid, the pasteurian sporosarcina is activated and cultured into the second-generation pasteurian sporosarcina; the second-generation pasteurian sporosarcina and glycerol are uniformly mixed at a volume ratio of 7:3, and then the mixed second-generation pasteurian sporosarcina-glycerol mixed solution is placed in the liquid culture solution at a volume ratio of 1:100, and finally placed in a constant temperature oscillating box at 30°C and 180 rpm for culture to obtain a bacterial solution; The preparation method of the liquid culture solution is: Manganese sulfate, nickel chloride, ammonium chloride, yeast extract and deionized water were uniformly mixed in a mass ratio of 1:1:1000:2000:100000, adjusted to pH = 9.0 with NaOH solution, heated and sterilized in steam for 35 minutes, and then cooled at room temperature for later use; The preparation method of the cementing liquid is: The urea solution of equal concentration and volume was uniformly mixed with the anhydrous calcium chloride solution to obtain a cementing solution with a concentration of 1 mol / L; Step 3: Weigh a certain mass of the sand sample prepared in step 1, add the solidifying liquid prepared in step 2, which accounts for 16% of the mass ratio of the sand sample, and mix evenly to obtain a sand material; Step 4: Add 2% of calcium saccharide by mass to the sandy soil material obtained in step 3, and mix evenly to obtain calcium saccharide-sandy soil material; Step 5: compact the sugar calcium-sand material obtained in step 4 in 3 layers, with each layer compacted to a height of 27 mm. Scrape the layers apart, and place at 35° C. for 7 days to solidify and cure to obtain a solidified sand body.
5. A method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium, characterized in that: The specific steps include: Step 1: air-dry the natural aeolian sand, and then filter it through a 0.6 mm mesh sieve to obtain a sand sample with impurities removed; Step 2: Mix the bacterial liquid and the cementing liquid in a volume ratio of 1:2 and stir to form a solidifying liquid; The bacterial liquid preparation method is as follows: In a sterile environment, 0.2 g of pasteurian sporosarcina is inoculated into 50 mL of liquid culture solution, and the solution is placed in a constant temperature shaking box at 35°C and 170 rpm for activation culture. When the liquid culture solution becomes turbid, the pasteurian sporosarcina is activated and cultured into the second-generation pasteurian sporosarcina; the second-generation pasteurian sporosarcina and glycerol are uniformly mixed at a volume ratio of 6:4, and then the mixed second-generation pasteurian sporosarcina-glycerol mixed solution is placed in the liquid culture solution at a volume ratio of 1.5:200, and finally placed in a constant temperature shaking box at 35°C and 170 rpm for culture to obtain a bacterial solution; The preparation method of the liquid culture solution is: Manganese sulfate, nickel chloride, ammonium chloride, yeast extract and deionized water were uniformly mixed in a mass ratio of 1:1.5:2000:3000:150000, adjusted to pH=8.5 with NaOH solution, heated and sterilized in steam for 30 minutes, and then cooled at room temperature for later use; The preparation method of the cementing liquid is: The urea solution of equal concentration and volume was uniformly mixed with the anhydrous calcium chloride solution to obtain a cementing solution with a concentration of 1.5 mol / L; Step 3: Weigh a certain mass of the sand sample prepared in step 1, add the solidifying liquid prepared in step 2, which accounts for 18% of the mass ratio of the sand sample, and mix evenly to obtain a sand material; Step 4: Add 4% of sugar calcium to the sandy soil material obtained in step 3, and mix evenly to obtain sugar calcium-sandy soil material; Step 5: compact the sugar calcium-sand material obtained in step 4 in 4 layers, with each layer compacted to a height of 20 mm. Scrape the layers apart, and place at 37° C. for 6 days to solidify and cure, to obtain a solidified sand body.
6. A method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium, characterized in that: The specific steps include: Step 1: air-dry the natural aeolian sand, and then filter it through a 0.7 mm mesh sieve to obtain a sand sample with impurities removed; Step 2: Mix the bacterial liquid and the cementing liquid in a volume ratio of 2:3 and stir to form a solidifying liquid; The bacterial liquid preparation method is as follows: In a sterile environment, 0.2 g of pasteurian sporosarcina is inoculated into 100 mL of liquid culture solution, and the solution is placed in a constant temperature shaking box at 40°C and 160 rpm for activation culture. When the liquid culture solution becomes turbid, the pasteurian sporosarcina is activated and cultured into the second-generation pasteurian sporosarcina; the second-generation pasteurian sporosarcina and glycerol are uniformly mixed at a volume ratio of 5:4, and then the mixed second-generation pasteurian sporosarcina-glycerol mixed solution is placed in the liquid culture solution at a volume ratio of 2:300, and finally placed in a constant temperature shaking box at 40°C and 160 rpm for culture to obtain a bacterial solution; The preparation method of the liquid culture solution is: Manganese sulfate, nickel chloride, ammonium chloride, yeast extract and deionized water were uniformly mixed in a mass ratio of 2:2:1500:3000:200000, adjusted to pH=8.0 with NaOH solution, heated and sterilized in steam for 40 minutes, and then cooled at room temperature for later use; The preparation method of the cementing liquid is: The urea solution of equal concentration and volume and the anhydrous calcium chloride solution are uniformly mixed to obtain a cementing solution with a concentration of 2 mol / L; Step 3: Weigh a certain mass of the sand sample prepared in step 1, add the solidifying liquid prepared in step 2, which accounts for 18% of the mass ratio of the sand sample, and mix evenly to obtain a sand material; Step 4: Add 6% of calcium saccharide by mass to the sandy soil material obtained in step 3, and mix evenly to obtain calcium saccharide-sandy soil material; Step 5: compact the sugar calcium-sand material obtained in step 4 in 2 layers, with each layer compacted to a height of 40 mm. Scrape the layers apart, and place at 39° C. for curing for 5 days to obtain a cured sand body.
7. A method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium, characterized in that: The specific steps include: Step 1: air-dry the natural aeolian sand, and then filter it through a 0.8 mm mesh sieve to obtain a sand sample with impurities removed; Step 2: Mix the bacterial liquid and the cementing liquid in a volume ratio of 2:3 and stir to form a solidifying liquid; The bacterial liquid preparation method is as follows: In a sterile environment, 0.2 g of pasteurian sporosarcina is inoculated into 50 mL of liquid culture solution, and the solution is placed in a constant temperature shaking box at 35°C and 150 rpm for activation culture. When the liquid culture solution becomes turbid, the pasteurian sporosarcina is activated and cultured into the second-generation pasteurian sporosarcina; the second-generation pasteurian sporosarcina and glycerol are uniformly mixed at a volume ratio of 5:3, and then the mixed second-generation pasteurian sporosarcina-glycerol mixed solution is placed in the liquid culture solution at a volume ratio of 2:100, and finally placed in a constant temperature shaking box at 35°C and 150 rpm for culture to obtain a bacterial solution; The preparation method of the liquid culture solution is: Manganese sulfate, nickel chloride, ammonium chloride, yeast extract and deionized water were uniformly mixed in a mass ratio of 2:1:1000:4000:150000, adjusted to pH = 9.0 with NaOH solution, heated and sterilized in steam for 45 minutes, and then cooled at room temperature for later use; The preparation method of the cementing liquid is: The urea solution of equal concentration and volume and the anhydrous calcium chloride solution are uniformly mixed to obtain a cementing solution with a concentration of 2 mol / L; Step 3: Weigh a certain mass of the sand sample prepared in step 1, add the solidifying liquid prepared in step 2, which accounts for 20% of the mass ratio of the sand sample, and mix evenly to obtain a sand material; Step 4: Add 6% of calcium saccharide by mass to the sandy soil material obtained in step 3, and mix evenly to obtain calcium saccharide-sandy soil material; Step 5: compact the sugar calcium-sand material obtained in step 4 in 3 layers, with each layer compacted to a height of 27 mm. Scrape the layers apart, and place at 40° C. for curing for 7 days to obtain a cured sand body.
8. A method for solidifying aeolian sand and resisting wind erosion by combining microorganisms with sugar calcium, characterized in that: The specific steps include: Step 1: air-dry the natural aeolian sand, and then filter it through a 1.0 mm mesh sieve to obtain a sand sample with impurities removed; Step 2: Mix the bacterial liquid and the cementing liquid in a volume ratio of 3:2 and stir to form a solidifying liquid; The bacterial liquid preparation method is as follows: In a sterile environment, 0.1 g of pasteurian sporosarcina is inoculated into 100 mL of liquid culture solution, and the solution is placed in a constant temperature shaking box at 30°C and 130 rpm for activation culture. When the liquid culture solution becomes turbid, the pasteurian sporosarcina is activated and cultured into the second-generation pasteurian sporosarcina; the second-generation pasteurian sporosarcina and glycerol are uniformly mixed at a volume ratio of 5:5, and then the mixed second-generation pasteurian sporosarcina-glycerol mixed solution is placed in the liquid culture solution at a volume ratio of 1:300, and finally placed in a constant temperature shaking box at 30°C and 130 rpm for culture to obtain a bacterial solution; The preparation method of the liquid culture solution is: Manganese sulfate, nickel chloride, ammonium chloride, yeast extract and deionized water were uniformly mixed in a mass ratio of 2:2:2000:3000:200000, adjusted to pH=8.5 with NaOH solution, heated and sterilized in steam for 35 minutes, and then cooled at room temperature for later use; The preparation method of the cementing liquid is: The urea solution of equal concentration and volume was uniformly mixed with the anhydrous calcium chloride solution to obtain a cementing solution with a concentration of 2.5 mol / L; Step 3: Weigh a certain mass of the sand sample prepared in step 1, add the solidifying liquid prepared in step 2, which accounts for 22% of the mass ratio of the sand sample, and mix evenly to obtain a sand material; Step 4: Add 8% of sugar calcium to the sandy soil material obtained in step 3, and mix evenly to obtain sugar calcium-sandy soil material; Step 5: compact the sugar calcium-sand material obtained in step 4 in 4 layers, with each layer compacted to a height of 20 mm. Scrape the layers apart, and place at 35° C. for curing for 5 days to obtain a cured sand body.
Citation Information
Cited By
Method for strengthening mechanical property of broken cap layer of underground gas storage
CN121324139A
